Supplemental Vitamin E a requirement for optimizing fecundity rates and litter size in sows - Umesiobi, Dennis O. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2008)
A total of 60 Large White gilts were randomly allotted to three groups (20 gilts per group) from coitus to lactation phases over a two-parity period to evaluate the effects of dietary vitamin E on fecundity rates and litter size of sows. Each of the three dietary vitamin E treatment combinations involved 0, 40 or 70 IU per kg of dl- α-tocopheryl acetate per kg of diet, and parity 1 and 2. Sow serum α-tocopherol and Selenium (Se) were collected on the 30th d post coitum, 99th d of gestation and 21st d of lactation. Serum α-tocopherol and Se were collected from piglets at 1 d post birth and 21 d weaning age. Data relating to SOW fecundity and litter size were also recorded. Results indicated that body weights and body weight gains of sows and their litters increased significantly (P<0.01) by parity, increasing more from parities 1 to 2, mostly when dietary vitamin E was increased from 40-70 IU per kg diet. The highest total piglets and number of piglets born alive (12 ± 8.9 vs. 11 ± 0.1) were obtained at parity 2 when dietary vitamin E was increased to 70 IU per kg diet. There was an increase in weights of the piglets when dietary vitamin E was increased in the sow's diet. There was a dramatic increase in serum a- tocopherol following 40 and 70 IU per kg of vitamin E supplementation during the 30th and 99th d gestation and 21st d lactation periods as parity increased. Se concentrations were about three-fold lower in 70 IU per kg of the vitamin E supplemented group in parity 2 compared with the respective groups. In both parities, female piglets gave higher serum α-tocopherol and Se at both 2 d post birth and 21 d weaning periods compared with the male piglets. Based on the results, supplementing 70 IU per kg α-tocopheryl acetate in sow's diets appears to be most beneficial in optimizing fecundity rates in sows and the survival of their litters.